Perancangan Playbook Sebagai Pendukung Buku Tema 7 Bagi Siswa Kelas 1 di SDN Pisangcandi 2 Malang - Inggrit Mei Saraswati (MAVIS : Jurnal Desain Komunikasi Visual, 2019)
The learning activities of the second semester students at Pisangcandi 2 Elementary School in Malang used the theme 7 book with a concept containing a lot of writing, counting questions, and a prohibition on not allowing the Theme Book to be used as a worksheet. This has an impact on the lack of interest of students to use the book outside of school hours. Therefore, the solution to this problem is to make interactive books in the form of playbooks as supporters of Book Theme 7. In addition, the design of the playbook also aims to increase students' interest while learning and playing according to the theme of Book 7 outside of school hours. The method used in this design begins with the phase of making the playbook material concept, choosing the type of interactive to be used, making the design from character to layout, and the prototyping stage before going to the final stage. This design produced a playbook in the form of books using 3 interactive concepts, namely peek a boo, games, and participations with discussion of material namely living things and non-living things, animals, and plants.